Study on rheological properties of silica nanofluids modified asphalt binder. (1st March 2021) - He, Haiqi; Hu, Jiulong; Li, Rui; Shen, Chenchen; Pei, Jianzhong; Zhou, Bochao
Highlights: SiO2 NFs are suitable as a modifier to blend with asphalt binder. Compatibility of SiO2 NFs and asphalt binder are much better than SiO2 NPs. Fatigue resistance of asphalt binder can be improved by SiO2 NFs. SiO2 NFs can improve the low-temperature crack resistance of asphalt binder. Abstract: Due to the existence of the nanoparticles (NPs) agglomeration phenomena in nanometer silica (SiO2 ) modified asphalt binder, solvent-free SiO2 nanofluids (NFs) were applied in asphalt modification to solve this issue in this research. The main objective is to investigate the rheological properties of SiO2 NFs modified asphalt binder. Solvent-free SiO2 NFs were manufactured based on SiO2 nanoparticles (NPs) by surface functionalization, and subsequently utilized to modify base asphalt binder with various dosages of 1 wt%, 3 wt% and 5 wt%. Fourier transform infrared spectrometer (FTIR), X-ray diffractometer (XRD), scanning electron microscope (SEM) and thermogravimetric analyzer (TGA) were conducted to investigate the microstructure characteristics and thermal stability of SiO2 NFs. The results prove that the successfully manufactured SiO2 NFs are suitable as a modifier to blend with asphalt binder. In addition, the compatibility between SiO2 NFs and base asphalt binder was also observed by SEM, indicating that the dispersion of SiO2 NFs and the compatibility with asphalt binder are much better than SiO2 NPs. Moreover, the tests of rheological property such as temperature sweep (TS), multiple stress creep recovery (MSCR), linear amplitude sweep (LAS), frequency sweep (FS) and bending beam rheometer (BBR) were executed to analyze the rutting, fatigue and crack resistances of asphalt binder effected by the SiO2 NFs. A series of test results manifest that the addition of SiO2 NFs slightly reduces the rutting resistance at high temperatures, but is favorable to improving the fatigue life and low-temperature crack resistance of asphalt binder.